New Horizons in the Synthesis, Properties, and Applications of MXene Quantum Dots. Issue 5 (19th January 2023) - Sariga,; Babu, Ann Mariella; Kumar, Shashi; Rajeev, Rijo; Thadathil, Ditto Abraham; Varghese, Anitha
Abstract: The progress of MXenes, a 2D layered structural material since its discovery in 2011 recently arouses a great deal of attention due to their plethora of applications in a diverse range of fields. Their excellent properties in terms of surface chemistry, optical activity, electrical conductivity, presence of abundant active catalytic sites, tunable band gap structure, ease of surface functionalization, and good biocompatibility make them an ideal candidate. The authors aim to guide the readers through various aspects such as their unique properties, synthesis techniques, and the recent advancements associated with MXene quantum dots (QDs). Herein, this review serves as a one‐stop point for prospective researchers to gain a better understanding of the application of MXene QDs in various fields including electrochemical detection, biomedical applications, and energy conversion and storage applications. Abstract : The MXene quantum dots (QDs) gain wide attention due to excellent properties in terms of surface chemistry, optical activity, electrical conductivity, presence of abundant active catalytic sites, tunable band gap structure, ease of surface functionalization, and good biocompatibility. This review focuses on recent advancements in MXene QDs in different fields such as electrochemical detection, biomedical applications, and energy conversion and storage applications.